Communication For Development (C4D) and Environmental Sustainability in Nigeria - Nwokeocha, Ifeanyi Martins; Obi, Adaku Promise (CV. Rayyan Dwi Bharata, 2025)
Communication for Development (C4D) strategies hold transformative potential in promoting environmental sustainability in Nigeria, particularly within diverse communities facing critical ecological challenges. This study investigates how C4D strategies have influenced environmental awareness and knowledge among the Nigerian populace through a qualitative approach. The study adopted three objectives: examine the extent to which C4D strategies have been utilised in promoting environmental awareness and knowledge among the Nigerian populace; identify the challenges associated with the application of C4D strategies in promoting environmental sustainability in Nigeria; and explore the opportunities for effective utilisation of C4D strategies in promoting environmental sustainability in Nigeria. The study founded its roots on the Diffusion of Innovation Theory (DOI) and Social Cognitive Theory (SCT). Interviews conducted across three Local Government Areas in Akwa Ibom: Eket, Onna, and Esit Eket reveal varying degrees of effectiveness in C4D implementations, highlighting both successes and challenges. While the advancement of mobile communications and social media platforms offers substantial outreach opportunities, barriers such as limited resources, cultural misalignment, and ineffective communication channels persist. Nonetheless, findings suggest potential pathways for enhancing C4D strategies by focusing on local contexts, fostering multi-stakeholder collaboration, and empowering communities toward proactive environmental stewardship. This research underscores the necessity of adapting C4D initiatives to resonate with local cultural frameworks and addresses the vital role of inclusive participation in achieving sustainable environmental outcomes in Nigeria.